APLIKASI PEMASARAN PERUMAHAN PADA CV. MUJUR MAJALENGKA UTAMA BERBASIS WEB - Fauziah Fauziah; didi karmadi (Universitas Kuningan, 2018)
As the times progressed, world population growth is grew rapidly. This leads to increased demand for residence or house. Because of that, emerged one of the new promising business forms, namely is the residential business. Residential is a group of houses that function as a residence environment. The houses built have a type that indicates the area of the house with specifications. As with any other type of business, the residential business is not spared from marketing process. This of course aims to attract consumers to buy a house from the residential and so that the management company is able to gain profit faster. Typically with other business, residential marketing is done at crowded places by opening or renting a booth in the place while handing out flyers. In each booth, marketing employees provide residential information to visitors or potential buyers. But now, due to the rapid development of information technology and supported by internet technology that is currently very advanced, business peoples have started to use this technology as a media of business transactions. The Internet provides many advantages, including providing time efficiency and enabling the area of product marketing to be broader than traditional marketing. This of course can also be applied in residential business, where, to obtain time efficiency in accessing information of residential marketed and expansion of marketing area, the internet can be utilized for new business media, that is by building a web based marketing application. The residential marketing application web-based is using PHP as a programming language and MySQL as Database and Waterfall as software development techniques.Keywords: Residential Marketing, PHP, MySQL, Waterfall, CV. Mujur Majalengka.